3 / ( x+ 3) + 2 / ( x -3) + 3 / ( x - 3) ·( x +3) = cu numitor ( x -3)·( x +3)
= [ 3 ·( x -3) + 2 · ( x +3) + 3 ] / ( x -3) ·( x +3) =
= [ 3x - 9 + 2x + 6 + 3 ] / ( x -3) ·( x +3) = 5x / ( x -3) ·( x +3)
- 9 + 9 = 0
si 1 + ( x² + 9 ) / ( x² - 9 ) = [ x² - 9 + x² + 9 ] / ( x² - 9) = 2x² / ( x² - 9)
- 9 + 9 = 0
ex : 5x / (x -3) ·( x + 3) : 2x² ( x² - 9 ) =
= 5x · ( x² - 9 ) / 2x² · ( x -3) ·( x +3) =
= 5x · ( x -3) ·( x +3) / 2x² · ( x -3) ·( x +3 )
simplificam cu ( x -3) · ( x +3)
= 5x / 2x² = 5 / 2x
/ impartire